Implementasi Akad Murabahah Pada Pembiayaan Rumah Non Bank Di Puri Nirana Cigelam Purwakarta - Ratna Patmawati (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
This study discusses how to determine the Margin Murabaha in the purchase or financing agreement, what constraints faced in the determination of Margin, what efforts are made in the implementation of Murabahah agreement on the financing of non-bank housing and how the consumer response to the application of murabahah contract in Puri Nirana Cigelam. This research uses descriptive qualitative method by using primary data and secondary data. The result of the research shows that margin acceptance in murabahah agreement based on agreement, the agreement is 10%, in reality the margin obtained in every year is less than 10%. There is no constraint in determining the margin in the murabaha scheme that has been implemented in Puri Nirana Cigelam, Murabahah scheme implementation in the financing of non-bank house in Puri Nirana Cigelam is signing the agreement of both parties between the developers who sell the house and the consumer who bought the house with the clarity of price and payment flat as well as the margin or profit setting that both parties agree on. Consumer response to the implementation of murabahah agreement in Puri Nirana Cigelam castle that many agree and good, average, so the existence of Puri Nirana Cigelam, akad applied in Puri Nirana Cigelam, Islamic Concepts and Value Syari'ah and facilities provided by the PNC is the reason consumers choose to buy housing in Puri Nirana Cigelam.